PENINGKATAN PRODUKTIVITAS MELALUI USAHA WASTE REDUCTION DENGAN PENDEKATAN GREEN PRODUCTIVITY (STUDI KASUS: PT ECCO TANNERY INDONESIA) - Moses L. Singgih (Purifikasi, 2008)
PT ECCO Tannery Indonesia as one of leading tannery industry has a high waste disposal potential in its daily operation. For such thing, it is necessary for the management to have an appropriate environmental management such as waste reduction. This research tried to address this problem with Green Productivity (GP) approach, so that efforts in waste reduction could provide improvement of environmental performance and productivity. The waste reduction alternatives was further formulated, and chosen to be implemented according to financial analysis and alternative contribution estimation either to the productivity level or to the EPI index level. Results of this research were expected to provide solution of the high waste volume problem, which had to be sent to PT Prasadha Pamunah Limbah Industri (PPLI) Bogor. The waste reduction was on the decreasing sludge and fleshy waste quantity by using sludge drying machine with a capacity of 15 tonne/day, which could dry the waste until 90% dry solid. This alternative contributed the productivity enhancement up to 0.91% and improved the environmental performance through waste volume reduction to be disposed of to PPLI Bogor of about 66.9%.